Human 4.0 From Biology to Cybernetic - Rybarczyk, Yves (IntechOpen, 2021)
Information technology is becoming ingrained in our everyday life. The consequence of this is that the line between humans and technology is more and more blurred, and tends to transform the human being into a cyber-organism. This transformation, accompanied by the emergence of Industry 4.0, brings us to define a new term: Human 4.0. This new generation of individuals has to deal with smart interconnected pervasive environments supported by the internet of things. Nevertheless, this merge between humans and technology is not straight-forward and requires an additional effort to reduce the gap between the human being and the machine. Such research implies a multidisciplinary approach to the interaction between biological organisms and artificial artefacts. This book intends to provide the reader with an insight into the new relationship with the technology brought about by Industry 4.0, and how it can make the human-machine interaction more efficient.